If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3m=6m+6
We move all terms to the left:
3m-(6m+6)=0
We get rid of parentheses
3m-6m-6=0
We add all the numbers together, and all the variables
-3m-6=0
We move all terms containing m to the left, all other terms to the right
-3m=6
m=6/-3
m=-2
| 7p+9=10p | | -1+x=-x+17 | | –10+8j=9j | | -30=x-13 | | 1/x+8+1/x+9/2=1/x | | x-6.2=3.3 | | 400=10/x | | X=-y-8 | | 176=8x2x | | 3(4x+5)=-33+36 | | 8(4x-12)=3 | | x/2-15=-5 | | (3x+9)=123 | | A(x)=25+10x | | 10x-3(5/8x+6.7)=12.4 | | 8x-48=360 | | 3.5+10m=8.41 | | 2(8+y)+3y=156 | | 4(x+4+2x=52 | | 0=n^2-n-20=0 | | 13v=36-7v | | F(x)=80-15x | | 1/9x+4=5 | | |9x|=x^2-10 | | (6-i)(6+7i)=0 | | 13+7=-4(7x-5) | | -14+49=-5(x+1) | | 55y=220 | | -9(x-9)-6=75 | | 2(3n-8)=-8(1+7n) | | 4(t−3)+8=4(2t−4) | | -1.2x=0.3 |